2011
DOI: 10.5588/ijtld.10.0205
|View full text |Cite
|
Sign up to set email alerts
|

Why are tuberculosis patients not treated earlier? A study of informal health practitioners in Bangladesh

Abstract: Patients seeking care from informal practitioners access care more promptly, but have prolonged delays in initiating treatment. Further investigation on how to involve these practitioners in the programme should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 0 publications
5
27
1
1
Order By: Relevance
“…This behaviour can cause a marked delay in starting appropriate TB medication, given the fact that TB medication in line with the NTP guideline is seldom present in the informal health sector. This has been observed in earlier studies from Bangladesh 4. Our study adds the important finding that this preference of the informal sector persists throughout the care seeking trajectory.…”
Section: Discussionsupporting
confidence: 86%
“…This behaviour can cause a marked delay in starting appropriate TB medication, given the fact that TB medication in line with the NTP guideline is seldom present in the informal health sector. This has been observed in earlier studies from Bangladesh 4. Our study adds the important finding that this preference of the informal sector persists throughout the care seeking trajectory.…”
Section: Discussionsupporting
confidence: 86%
“…12,21-23 However, we did not fi nd any signifi cant associations between sex and treatment delay in our study. The fi ndings from our study are consistent with those of another study conducted in Bangladesh, 7 in which the researchers found no signifi cant association between sex and treatment delay. Another contradictory fi nding was the association of informal health care with treatment delay.…”
Section: Other Findingssupporting
confidence: 83%
“…In that study, 52% of patients with treatment delays consulted informal providers fi rst (Pearson χ 2 , P < 0.05). 7 However, in our study, no signifi cant association was found between informal health care providers and treatment delays. In the study by Rifat et al, respondents were recruited from both urban and rural areas.…”
Section: Other Findingscontrasting
confidence: 49%
See 1 more Smart Citation
“…Most of these deaths reflect diagnosis that is either delayed, missed, or never attempted. Strategies for improving TB diagnosis generally take one of three forms: (1) improvement of the "passive" diagnostic system (e.g., deploying new diagnostic tools, such as Xpert MTB/RIF [5,6] for diagnosis of people who present with TB symptoms); (2) "enhanced" diagnosis that aims to reduce delays in diagnosis for patients with recognizable symptoms, such as community awareness campaigns (7) and improved access to TB diagnostic services (8); and (3) "active" strategies that do not rely on patient presentation (e.g., household surveys [9], contact investigations [10]). The factors that determine the comparative effectiveness of these strategies in reducing populationlevel TB incidence remain largely unknown.…”
mentioning
confidence: 99%